New Plasmids for Fusarium Transformation Allowing Positive-Negative Selection and Efficient Cre-loxP Mediated Marker Recycling - Twaruschek, Krisztian; Spörhase, Pia; Michlmayr, Herbert; Wiesenberger, Gerlinde; Adam, Gerhard (Frontiers in Microbiology, 2018)
In filamentous fungi such as Fusarium graminearum, disruption of multiple genes of interest in the same strain (e.g. to test for redundant gene function) is a difficult task due to the limited availability of reliable selection markers. We have created a series of transformation vectors that allow antibiotic-based selection of transformants and subsequent negative selection for marker removal using thymidine kinase fusions combined with the Cre-loxP system. The fusion genes contain commonly used C-terminal drug resistance markers, either nptII (G418), nat1 (nourseothricin), or hph (hygromycin B). These resistance genes are fused to the sequence encoding HSVtk (Herpes simplex virus thymidine kinase). Despite the presence of the 1 kb HSVtk gene (about ~30% increase in total marker size), there is only a slight reduction in transformation efficiency on a molar basis. The fusion genes expressed under the Trichoderma pyruvate kinase promoter also confer antibiotic resistance in Escherichia coli, allowing straightforward construction of disruption plasmids. For removal of the loxP flanked resistance cassettes, protoplasts of transformants are directly treated with purified Cre recombinase protein. Loss of the HSVtk containing cassette is selected by restoration of resistance to 5-fluoro-2-deoxyuridine (FdU). As a proof of principle, we demonstrated the efficiency of the HSVtk-based marker removal in Fusarium by reversing the disruption phenotype of the gene responsible for production of the red pigment aurofusarin. We first disrupted the FgPKS12 gene via integration of the loxP-flanked HSVtk-nptII cassette into the promoter or the first intron, thereby generating transformants with a white mycelium phenotype. Using Cre recombinase and FdU, the selection marker was subsequently removed, and the resulting transformants regained red pigmentation despite the remaining loxP site. We also found that it is possible to remove several unselected loxP-flanked cassettes with a single Cre protein treatment, as long as one of them contains a negative selectable HSVtk cassette. The negative selection system can also be used to introduce allele swaps into strains without leaving marker sequences, by first disrupting the gene of interest and then complementing the deletion in situ with genomic DNA containing a different allele.